Challenges posed to professional practice of Social Work in Brazil in times of neoliberal globalization - Ribeiro, Edaléa Maria (Cuadernos de Trabajo Social, 2014)
This theoretical study aims to present an overview of the professional practice in Brazil, in times of neoliberal globalization. To this end, a brief introduction on the meaning and history of the profession, presents the debate on neoliberal globalization and its impacts on Brazilian soil. Outlines a series of questions that are posed to the social work professional nowadays and finally discusses the challenges posed to the occupation.